Determination of Nd3+ Ions in Solution Samples by a Coated Wire Ion-Selective Sensor - Hassan Ali Zamani (E-Journal of Chemistry)
A new coated wire electrode (CWE) using 5-(methylsulfanyl)-3-phenyl-1H-1,2,4-triazole (MPT) as an ionophore has been developed as a neodymium ion-selective sensor. The sensor exhibits Nernstian response for the Nd3+ ions in the concentration range of 1.0×10−6-1.0×10−2 M with detection limit of 3.7×10−7 M. It displays a Nernstian slope of 20.2±0.2 mV/decade in the pH range of 2.7–8.1. The proposed sensor also exhibits a fast response time of ∼5 s. The sensor revealed high selectivity with respect to all common alkali, alkaline earth, transition and heavy metal ions, including members of the lanthanide family other than Nd3+. The electrode was used as an indicator electrode in the potentiometric titration of Nd(III) ions with EDTA. The electrode was also employed for the determination of the Nd3+ ions concentration in water solution samples.